Overexpression of COL11A1 by cancer-associated fibroblasts: clinical relevance of a stromal marker in pancreatic cancer. - Carmen García-Pravia; José A Galván; Natalia Gutiérrez-Corral; Lorena Solar-García; Eva García-Pérez; Marcos García-Ocaña; Jokin Del Amo-Iribarren; Primitiva Menéndez-Rodríguez; Juan García-García; Juan R de Los Toyos; Laureano Simón-Buela; Luis Barneo (PLoS ONE, 2013)
BACKGROUND:The collagen11A1 (COL11A1) gene is overexpressed in pancreatic cancer. The expression of COL11A1 protein could be involved in desmoplastic events in pancreatic cancer, but an antibody that specifically stains the COL11A1 protein is not currently available. METHODS AND FINDINGS:A total of 54 pancreatic ductal adenocarcinomas (PDAC), 23 chronic pancreatitis (CP) samples, and cultured peritumoral stromal cells of PDAC (passages 3-6) were studied. Normal human pancreas tissue samples were obtained through a cadaveric organ donation program. 1) Validation of COL11A1 gene overexpression by q-RT-PCR. FINDINGS:the expression of COL11A1 gene is significantly increased in PDAC samples vs. normal and CP samples. 2) Analysis of COL11A1 by immunohistochemistry using highly specific anti-proCOL11A1 antibodies. FINDINGS:anti-proCOL11A1 stains stromal cells/cancer-associated fibroblasts (CAFs) of PDAC but it does not stain chronic benign condition (chronic pancreatitis) stromal cells, epithelial cells, or normal fibroblasts. 3) Evaluation of the discrimination ability of the antibody. FINDINGS:anti-proCOL11A1 immunostaining accurately discriminates between PDAC and CP (AUC 0.936, 95% CI 0.851, 0.981). 4) Phenotypic characterization of proCOL11A1+ stromal cells co-staining with mesenchymal, epithelial and stellate cell markers on pancreatic tissue samples and cultured peritumoral pancreatic cancer stromal cells. FINDINGS:ProCOL11A1+ cells present co-staining with mesenchymal, stellate and epithelial markers (EMT phenotype) in different proportions. CONCLUSIONS/SIGNIFICANCE:Detection of proCOL11A1 through immunostaining with this newly-developed antibody allows for a highly accurate distinction between PDAC and CP. Unlike other available antibodies commonly used to detect CAFs, anti-proCOL11A1 is negative in stromal cells of the normal pancreas and almost absent in benign inflammation. These results strongly suggest that proCOL11A1 is a specific marker for CAFs, and thus, anti-proCOL11A1 is a powerful new tool for cancer research and clinical diagnostics.